Induction of tryptophan 2,3-dioxygenase expression in human monocytic leukemia/lymphoma cell lines THP-1 and U937 - Hoffmann, D; Pilotte, L; Stroobant, V; Van Den Eynde, B (SAGE Publications, 2019)
Tumor-associated macrophages are immune cells with diverse functions in tumor development. Among other functions, they downregulate immune-mediated tumor rejection by depriving lymphocytes of nutrients. The essential amino acid tryptophan is metabolized by the enzymes indoleamine 2,3-dioxygenase 1 and tryptophan 2,3-dioxygenase (TDO). Indoleamine 2,3-dioxygenase 1 is expressed in a large number of human tumors, and inhibitors are in development to improve immunotherapy. Tryptophan 2,3-dioxygenase was also found in human tumors and preclinical working models confirmed its immunosuppressive power. We explored a potential expression of TDO by macrophages. This enzyme could be induced in two human cell lines, THP-1 and U937, by incubation with phorbol myristate acetate, lipopolysaccharide, and interferon gamma. Phorbol-myristate-acetate-mediated induction was inhibited by rottlerin, a protein kinase C inhibitor. In contrast to these monocytic cell lines, other cell lines or fresh human monocytes isolated from peripheral blood mononuclear cells and differentiated into proinflammatory or anti-inflammatory macrophages could not be induced to express TDO. Our results suggest that TDO might play an immunosuppressive role in human monocytic leukemias but not in untransformed macrophages.